MEMBANGUN PARADIGMA AKUNTASI SYARIAH - Arwani, Agus (Khatulistiwa, 2012)
Although the history of accounting stretches back to when the first organised society began, accounting theory development is mainly a child of the 20th Century. Although the profession began in the UK in 1853 in Scotland, it is in the USA accounting theory development took place with the contribution of academics and the participation of the profession. The accountability framework is discussed and proposed as an alternate framework. The reasons why this framework would be the most likely to be the one adopted in any Islamic accounting are given. The philosophy, ontology and epistemology of the Islamic worldview are given as a background to the need for of Islamic accounting. These are then discussed in the light of objectives of the Islamic syariah on which Islamic accounting would have to be based. The objectives of Islamic accounting are then discussed with the implication for Islamic accounting concepts, principles and reporting practices. It is concluded that Islamic accounting is part of the evolution of accountancy to a more holistic approach that takes into account the socio/political/natural environments and as an attempt to liberate accounting from its incarceration in the utilitarian economic domain.